Estimation of Anisotropy Parameters, δ and ε: An Application to Borehole and Seismic Data from Ketzin, Germany - Mingkhwan Kruachanta (Science Faculty of Chiang Mai University, 2020)
Weak anisotropy was indicated in a previous investigation of the 3D baseline seismic data acquired through the EU funded CO2SINK project at the Ketzin pilot site for CO2 storage, Germany. Fourth order velocity analysis yielded the Alkhalifah anellipticity factor, or eta (η), ranging from -0.2399 to 0.1341 for the whole study area. Although application of the simple η term in the moveout correction allowed reflections to be flattened at far offsets, resulting in an improved seismic stacked section, the Thomsen parameters, delta (δ) and epsilon (ε) are of greater interest from a rock physics perspective. Borehole data from Ketzin were introduced to estimate δ and ε using known relationships between sonic wave velocity, NMO velocity, η, δ and ε. In this paper, δ and ε estimations were performed using data from three wells; the CO2 injection well and two observation wells. Preliminary estimates of the Thomsen parameters give δ ranging from -0.2658 to -0.1270, while ε ranges from -0.2611 to -0.1141. These δ and ε values also indicate the presence of weak vertical transverse isotropy at the site, which is consistent with the previous study.